Recent breakthroughs in two-dimensional van der Waals magnetic materials and emerging applications. (October 2020) - Khan, Yahya; Obaidulla, Sk. Md.; Habib, Mohammad Rezwan; Gayen, Anabil; Liang, Tao; Wang, Xuefeng; Xu, Mingsheng
Graphical abstract: Highlights: This comprehensive review article consists of history, recent progress and future development in order to promote the 2D magnetism field. This article covers chemical structures and synthesis methods of 2D magnetic materials, techniques for characterizing magnetic properties. This article further elaborates the device applications and challenges faced in this emerging field of 2D magnetism. Developments of both intrinsic and extrinsic 2D magnetic materials originating from external stimuli such as doping and strain are presented. The very recent advances of intrinsic magnetism in 2D materials and devices are concentrated on backgrounds of physics and material structures. Abstract: Two-dimensional (2D) magnetism is now the attention of central demands in fundamental condensed matter physics concerning about the understanding and control of new phases. The demonstration of ferromagnetism in an atomically thin layer develops the prospects for a variety of device applications of 2D van der Waals (vdW) materials. The long-range ferromagnetic ordering in 2D vdW crystals together with their fascinating electric and optical properties will lead to magnetic, magneto-electric, and magneto-optic applications. Low-power, high-speed, and ultra-compact spintronic devices, data storage, information recognition and processing, smart sensors, and quantum computing applications are highly necessary for future industrial applications. This review covers the fundamental chemical structures and synthesis methods of 2D magnetic materials, the techniques for characterizing magnetic properties, device applications and the challenges faced in this emerging field. The progress in both intrinsic and extrinsic magnetic 2D materials originated from external stimuli such as doping, defects, functionalization, and strain is emphasized. The comparison of fundamental physics, chemistry, and related issues of vdW 2D magnetic materials with other-dimensional counterparts concentrated on backgrounds is also emphasized. We focus on the design of chemical and crystal structures leading to 2D magnetism, detailed chemical and physical properties and the device applications of vdW 2D magnetism. Finally, challenges and outlooks in the realization of 2D magnetism are discussed and believed that this emerging field will excite more intensive research and provide exceptional breakthroughs in the field of spintronics.